The impact of communication on attitudes toward death: Exploring the importance of effective communication in shaping perceptions and perspectives in Malaysia - Ngah, Farhah Hanun; Sitinjak, Charli; Manap, Jamiah; Kasim, Arena Che (Journal of Asian Scientific Research, 2025)
This study looks at the effect of communication on attitudes around death in a sample of 250 Malaysians from various locations. The Death Attitude Profile-Revised (DAP-R) and the Multidimensional Fear of Death Scale (MFODS) were employed to examine participants' attitudes about death. The findings reveal a connection between good death communication, more positive views toward death, and less fear of dying. On the DAP-R scale, participants indicated a moderate attitude toward death, with a higher fear of death than acceptance of death on the MFODS subscales. There were gender disparities, with males having slightly more positive attitudes toward death than females. However, the study has significant limitations, including a cross-sectional methodology and a sample from Malaysia, which restrict the findings' generalizability. Future research should include longitudinal studies and a broader spectrum of subjects to improve the validity and generalizability of the results. The findings underline the significance of effective communication in developing views and perspectives on death, emphasizing the need for educational programs and interventions to improve end-of-life conversations and encourage positive attitudes toward death. Future studies should investigate additional demographic aspects, employ qualitative methods and observational studies, and assess the effectiveness of various communication styles and treatments. By filling these gaps, we can improve our understanding of the function of communication in death attitudes and contribute to creating compassionate and supportive end-of-life care practices.